Analysis of congenital syphilis notifications in a university hospital in the city of Niterói from 2016 to 2020 - Gonçalves, Andrea Menezes; Fernandes, Carolina Batista; Messias, Ilana Rangel; Barcante, Stephanie; Morais, Julia Sampaio de Souza; Camacho, Julia Sampaio Fernandes; Bravo, Renato de Souza; Barbosa, Adauto Dutra Moraes; Ferry, Fernando Raphael de Almeida (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The elimination of congenital syphilis is a challenge in the field of public health worldwide. The failure of previous global plans forces authorities to rethink detection and control strategies, with compulsory notification being an important tool for obtaining data. Objective: To analyze the notifications of congenital syphilis made by Departamento de Vigilância Epidemiológica do Hospital Universitário Antônio Pedro (Department of Epidemiological Surveillance at Antônio Pedro University Hospital), between January 2016 and August 2020. Methods: Retrospective, descriptive, and quantitative study of data from congenital syphilis notification forms in Hospital Universitário Antônio Pedro from January 2016 to August 2020. In the descriptive analysis of categorical variables, absolute and relative frequencies were used; for numerical measures, central tendency and dispersion measures were used. Spearman correlation, Mann-Whitney test and Fisher’s exact test were performed in the R software (version 4.0.3). Hills’ criteria for causality were also considered. Results: Of the 67 forms examined, two were excluded due to duplication, and 48 variables were analyzed. No form was completely filled out, and some data were missing on more than 90% of them. According to maternal data, patients were mostly from Niterói (60%), had an average age of 23.09 years, and were brown (32.31%), while 13.85% did not finish 5th to 8th grade and 80% had prenatal care, but less than half had appropriate treatment indicated. As for the children: 55.38% were female, 40% brown, with an average age of 90.98 days. The great majority (72.31%) of them were born at Hospital Universitário Antônio Pedro, and not being born at this hospital was significant when it came to being asymptomatic (69.23%, p=0.001); the most frequent symptom was jaundice. Conclusion: Improvement in the follow-up and investigation of the reported cases can significantly decrease this high percentage of missing information, improving the quality of the data. The vast majority of patients underwent prenatal care, and therefore, they were avoidable cases, since the maternal diagnosis in the peripartum period occurs when the chance for vertical transmission has already occurred and caused consequences for the child’s life.